Managing risk in cancer presentation, detection and referral: a qualitative study of primary care staff views. Issue 6 (12th June 2014) - Cook, Neil; Thomson, Gillian; Dey, Paola
Abstract : Objectives: In the UK, there have been a number of national initiatives to promote earlier detection and prompt referral of patients presenting to primary care with signs and symptoms of cancer. The aim of the study was to explore the experiences of a range of primary care staff in promoting earlier presentation, detection and referral of patients with symptoms suggestive of cancer. Setting: Six primary care practices in northwest England. Participants: 39 primary care staff from a variety of disciplines took part in five group and four individual interviews. Results: The global theme to emerge from the interviews was 'managing risk', which had three underpinning organising themes: 'complexity', relating to uncertainty of cancer diagnoses, service fragmentation and plethora of guidelines; 'continuity', relating to relationships between practice staff and their patients and between primary and secondary care; 'conflict' relating to policy drivers and staff role boundaries. A key concern of staff was that policymakers and those implementing cancer initiatives did not fully understand how risk was managed within primary care. Conclusions: Primary care staff expressed a range of views and opinions on the benefits of cancer initiatives. National initiatives did not appear to wholly resolve issues in managing risk for all practitioners. Staff were concerned about the number of guidelines and priorities they were expected to implement. These issues need to be considered by policymakers when developing and implementing new initiatives.